Market Giants vs. Dwarfs: New Zealand’s Perspective on Environmental Reporting - Saman Bandara; Ahesha Perera (Indonesian Journal of Sustainability Accounting and Management, 2022)
This paper examines New Zealand listed firms’ compliance with Global Reporting Initiative-environmental reporting standards (GRI 300) and the impact of environmental reporting determinants on the level of sustainability reporting. The author collected data from annual and sustainability reports of the top and bottom 30 firms listed on the New Zealand Stock Exchange (NZX). The author then conducted content analysis to measure the extent of each firm’s environmental reporting score. The study findings indicate that large firms report only one-thirds of the relevant information, whereas small firms neither adopt international reporting frameworks nor report on the environment. Additionally, we found that firm size and profitability are positively associated with the extent of environmental reporting in New Zealand, whereas industry-specific differences play a minor role. This study further finds that firms, which explicitly referred to the “Global Reporting Initiatives” or “GRI” terms in their annual or sustainability reports, outperformed in environmental reporting compared with those that did not. This study uses GRI 300 standards to assess the level of environmental reporting of each firm. Finally, the study compares environmental reporting practices between top and bottom-listed firms in New Zealand. The findings emphasize the desirability of making the environment reporting mandatory in all companies to ensure the New Zealand Government’s latest enforcement of climate risk reporting.